PELANGGARAN PRINSIP KESOPANAN DALAM PODCAST PODHUB - Afdhilla, Afdhilla; Istiqamah, Istiqamah; Rahmaton, Rahmaton; Putri, Vicka Aulia (Universitas Batanghari, 2024)
Pragmatics is a branch of linguistics that studies the language used to communicate in certain situations. In a specific context, this definition means that apart from the language used to communicate, there are also other aspects that cannot be separated from linguistic research. This research aims to find out whether there are violations of the principle of politeness in the Podhub podcast episode with Prilly Latuconsina and Teuku Rizky. The method used in this research is a qualitative descriptive method and data collection techniques by listening to every word in the podcast carefully, thoroughly and seriously. The research results show that in the Podhub podcast there are violations of the principles of politeness in the form of the maxim of wisdom, the maxim of generosity, the maxim of acceptance, the maxim of humility, the maxim of suitability, and the maxim of sympathy.Keywords: Podcast, Podhub, Violation of the Principles of Decency